2021
DOI: 10.29392/001c.19141
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use and COVID-19 in Ghana: generating evidence to support policy and practice

Abstract: Background The COVID-19 pandemic has affected over 45 million people and caused over a million deaths globally. Tobacco use, a threat to public health worldwide, increases the risk of developing severe COVID-19 disease and death. The hand-to-mouth action, smoking-induced lung diseases, and the sharing of tobacco products such as water pipes, increase a smoker's vulnerability to COVID-19. Implementation of tobacco control efforts in low-and middle-income countries (LMICs) including sub-Saharan Africa (SSA) is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…In a study by Singh A et al, interviewees noted that lockdown restrictions offered an opportunity to promote cessation, in the context of reduced tobacco sales. 11 Our survey findings also emphasize that messages on ill effects of tobacco use and its impact on COVID- 19 should be widely disseminated. In a multicentric study by Pettrigew S et al, it was observed that smokers with intention to quit within 2 weeks rose to 38% from 32% after being exposed to messages about smoking related COVID-19 risk.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In a study by Singh A et al, interviewees noted that lockdown restrictions offered an opportunity to promote cessation, in the context of reduced tobacco sales. 11 Our survey findings also emphasize that messages on ill effects of tobacco use and its impact on COVID- 19 should be widely disseminated. In a multicentric study by Pettrigew S et al, it was observed that smokers with intention to quit within 2 weeks rose to 38% from 32% after being exposed to messages about smoking related COVID-19 risk.…”
Section: Discussionmentioning
confidence: 68%
“…Given the important role played by the media and formal education in discouraging smoking behaviour, these media messages could be used more intensively in disseminating relevant information on the dangers of smoking. 11 …”
Section: Discussionmentioning
confidence: 99%